PENGARUH MOTIVASI KERJA GURU TERHADAP SEMANGAT KERJA GURU PADA SMK MULTAZAM GISTING KABUPATEN TANGGAMUS LAMPUNG - Garaika, Garaika; Idris, Muhammad (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
The development of science and technology which is increasingly rapid, will make the competition for human resources increasingly stringent and competitive. In the process of improving the quality of human resources, the world of education plays a very important role. This role is related to efforts to make the next generation of the nation with reliable human resources. To improve the quality of human resources from the education sector, teachers are a key factor for achieving the success of an education. Multazam Gisting Vocational School is an institution that is engaged in education which aims to prepare and develop students thoroughly in the academic, psychological and social fields. As an educational institution that has the aim to educate the nation's life The results of identification of conditions that occur, directly or indirectly have implications for changes in work motivation, which in turn affects the morale of teachers. Based on data obtained from preliminary observations, it is obtained data that there is a decrease in teacher work motivation, showing that from 20 teachers the percentage of employee attendance has decreased, where until December 2018 employees were present only 85%. While absenteeism increased to 15%. The data is the low level of employee attendance indicates decreased work motivation. Based on data and analysis qualitatively and quantitatively in this study a conclusion can be drawn that there is a significant influence of teacher work motivation on teacher morale in Vocational School Multazam This is evidenced by a regression coefficient of 0.688, a significance of less than 0.05 of 0.000, the regression model Y = 18.720 + 0.668X1. The magnitude of the effect of employee communication on morale by the remaining 91% by 9% is influenced by other variables.